Innovative capability and financing constraints for innovation: More money, more innovation? - Hanna Hottenrott; Bettina Peters (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2009)
This study presents a novel empirical approach to identify financing constraints for innovation based on the idea of an ideal test as suggested by Hall (2008). Firms were offered a hypothetical payment and were asked to choose between alternatives of use. If they choose additional innovation projects they must have had some unexploited investment opportunities that were not profitable using more costly external finance. That is, these firms have been financially constrained. We attribute constraints for innovation not only to lacking financing, but also to firms' innovative capability. Econometric results show that financial constraints do not depend on the availability of internal funds perse, but that they are driven by innovative capability. We find firms with high innovative capability but low financial resources to be most likely subject to financing constraints. Yet, we also observe constraints for financially sound firms that may have to put ideas on the shelf.
More recent version: http://hdl.handle.net/10419/45853
Keywords: O31; O32; C35; 330; Innovation; financing constraints; innovative capability; multivariate probit models; Forschungsfinanzierung; Risikokapital; Verschuldungsrestriktion; Innovation; Probit-Modell; Schätzung; Deutschland